1993
DOI: 10.1007/bf01215985
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin-like growth factor receptors I and II in normal human lung and in lung cancer

Abstract: Insulin-like growth factors are potent mitogenic factors in human lung cancer in vitro, acting via specific receptors. Using monoclonal antibodies we demonstrate the expression of insulin-like growth factor receptor I in bronchial epithelial cells of normal lung and in primary lung cancer (22/24 cases), being most prominent in squamous cell carcinoma. Electron microscopy on lung cancer cell lines reveals a distinct reaction pattern on the plasma membrane. Immunoreaction with a specific antibody directed agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…In stratified analyses, the association was more predominant among patients receiving surgical operation, and there was a significant multiplicative interaction between risk genotypes and operation status. Both experimental and clinical studies have shown that the IGF-I receptor is overexpressed in lung and other carcinomas compared with normal tissues (34)(35)(36)(37), which might eliminate the downregulation effect of the variant genotypes of rs5742714 among patients without operation.…”
Section: Discussionmentioning
confidence: 99%
“…In stratified analyses, the association was more predominant among patients receiving surgical operation, and there was a significant multiplicative interaction between risk genotypes and operation status. Both experimental and clinical studies have shown that the IGF-I receptor is overexpressed in lung and other carcinomas compared with normal tissues (34)(35)(36)(37), which might eliminate the downregulation effect of the variant genotypes of rs5742714 among patients without operation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies demonstrated that continuously high levels of IGF-I over the life span would lead to deleterious consequences and contribute to pathological changes associated with age through the effect on cell division and/or metabolism. In fact, due to the effect of IGF-I on cellular replication, this hormone has also been linked to the development of several diseases such as cancer (32,75). Thus it could be hypothesized that the decrease in plasma IGF-I observed in long-lived subjects might minimize the generalized mitogenic stimulus to tissues and then contribute to the reduction of agerelated pathologies.…”
Section: Humansmentioning
confidence: 99%
“…In a transgenic carcinogenesis model involving simian virus 40 T antigen targeted to the ␤-islet cells, activation of the IGF-IR by IGF-II is a critical determinant of carcinogenic progression (8). Elevated levels of IGF-IR have been detected in human tumors of lung (22,32), breast (11,15,36), and colon (18,37), and this is often associated with increased levels of circulating IGF-I and/or IGF-II (4,29). For many such tumors, IGF-I acts as a mitogen in vitro (16,33), suggesting the involvement of IGF-IR autocrine or paracrine signaling loops in tumors in vivo (25,48).…”
mentioning
confidence: 99%